Novel truncating and missense mutations of the KCC3 gene associated with Andermann syndrome - ELÇİOĞLU, HURİYE NURSEL (LIPPINCOTT WILLIAMS & WILKINS, 2006)
Background: Andermann syndrome (OMIM 218000) is an autosomal recessive motor-sensory neuropathy associated with developmental and neurodegenerative defects. The cerebral MRI reveals a variable degree of agenesis of the corpus callosum. Recently, truncating mutations of the KCC3 gene (also known as SLC12A6) have been associated with Andermann syndrome. Methods: The authors assessed clinically and genetically three isolated cases from Germany and Turkey with symptoms consistent with Andermann syndrome. Results: The authors detected four novel mutations within the KCC3 gene in their patients: two different truncating mutations in the first patient, a homozygous truncating mutation in the second, and a homozygous missense mutation in the third patient. In contrast to the classic phenotype of the Andermann syndrome linked to truncating KCC3 mutations the phenotype and the course of the disease linked to the missense mutation appeared to be different (i. e., showing additional features like diffuse and widespread white matter abnormalities). Conclusions: Not only truncating but also missense mutations of the KCC3 gene are associated with Andermann syndrome. Different types of KCC3 mutations may determine different clinical phenotypes.
Keywords: K-CL COTRANSPORTER; CORPUS-CALLOSUM; SENSORIMOTOR NEUROPATHY; PERIPHERAL NEUROPATHY; FRENCH-CANADA; AGENESIS; NEURONOPATHY; CLONING